A review of process modeling for wood borer pests - Keenan, Vincent A.; Kanyamibwa, Moïse; Marion, Glenn; Touza, Julia; Kleczkowski, Adam (Frontiers in Forests and Global Change, 2026)
IntroductionWood borer pests represent a growing threat to forestry worldwide, with potential for an increase in climate change induced outbreaks that could significantly impact ecosystem functioning.MethodsThis study reviews the current state-of-the-art in bark beetle modeling as presented in peer-reviewed English language scientific papers and reviews cited in Clarivate Analytics Web of Science (WoS) Core Collection in the period from 2006 to 2023, but earlier influential papers cited in reviews from this period are also in scope. We categorize studies by modeling methodology, by host and by modeled processes.ResultsAsh, pine, and spruce hosts account for 88% of studies, the majority of which focus on the continental USA, British Columbia, Canada and Central Europe. In terms of methodology, statistical methods are the most commonly employed technique, and the majority of articles model just one or two key processes with pest demography and environmental factors being the most studied across different hosts. Commonalities in methods used across pest-host systems include: use of phenology-like models; application of static species distribution models (SDMs) to understand climate impacts; modeling of spread via local and long-range kernels; and use of economic cost-benefit analysis as a tool to guide management.DiscussionWe identify several gaps in current research including quantifying economic consequences of wood borer pests and the need for greater understanding of ecological impacts and resilience. Agent- and individual-based models may also provide useful tools for understanding the complexity of socio-ecological system dynamics. However, such developments should be in tandem with wider use of techniques for parameter estimation and uncertainty quantification, including Bayesian inference in particular of the dynamics of spatial spread. A related challenge is better quantification of pathways - including trade - for entry by invasive pests, coupled with a greater understanding of potential vulnerabilities of forest systems to environmental drivers like climate change, coupled with potentially multiple endemic, emerging and novel pests. Addressing these challenges would enable both better mitigation of risks associated with wood borer beetle infestations and better management of outbreaks when they do occur.